Structure of an early native‐like intermediate of β2‐microglobulin amyloidogenesis. (20th August 2013) - Vanderhaegen, Saskia; Fislage, Marcus; Domanska, Katarzyna; Versées, Wim; Pardon, Els; Bellotti, Vittorio; Steyaert, Jan
Abstract: To investigate early intermediates of β2‐microglobulin (β2m) amyloidogenesis, we solved the structure of β2m containing the amyloidogenic Pro32Gly mutation by X‐ray crystallography. One nanobody (Nb24) that efficiently blocks fibril elongation was used as a chaperone to co‐crystallize the Pro32Gly β2m monomer under physiological conditions. The complex of P32G β2m with Nb24 reveals a trans peptide bond at position 32 of this amyloidogenic variant, whereas Pro32 adopts the cis conformation in the wild‐type monomer, indicating that the cis to trans isomerization at Pro32 plays a critical role in the early onset of β2m amyloid formation. Abstract : PDB Code(s):4KDT